2015
DOI: 10.1016/j.ejrnm.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute pulmonary embolism by sixty-four slice multidetector CT angiography: Correlation between obstruction index, right ventricular dysfunction and clinical presentation

Abstract: Introduction: MDCT pulmonary angiography is the method of choice for the detection of pulmonary embolism (PE). The severity of PE as estimated by the obstruction index (OI) and right ventricular dysfunction (RVD) can be evaluated with MDCT. Objective: To investigate the correlation between the OI, RVD and clinical presentation in patients with acute PE. Methods: Among 70 patients with suspected PE, 35 patients proved to have PE with MDCT. The CT OI and the RV/LV diameter (RVD-ratio) using the four-chamber view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
1
14
0
2
Order By: Relevance
“…The results of the current investigation are consistent with those of the study conducted by Attia et al, which reported that the PAOI is correlated with dyspnea and tachycardia; however, they did not show any relationship with hemoptysis and chest pain, which are common in peripheral pulmonary embolisms (21). According to our results, Wells score can be used to evaluate the severity of PE similar to CT index.…”
Section: Discussionsupporting
confidence: 82%
“…The results of the current investigation are consistent with those of the study conducted by Attia et al, which reported that the PAOI is correlated with dyspnea and tachycardia; however, they did not show any relationship with hemoptysis and chest pain, which are common in peripheral pulmonary embolisms (21). According to our results, Wells score can be used to evaluate the severity of PE similar to CT index.…”
Section: Discussionsupporting
confidence: 82%
“…[ 26 ] There are several scoring systems reported to evaluate the pulmonary vascular tree and assessment of clot burden score. [ 16 ] The present study quantified clot burden scoring according to QS as it is more objective, easy to calculate, distinguish between partial and complete obstruction, and has less interobserver variability. [ 13 19 ] Serial imaging studies could be used to assess the degree of vascular obstruction which helps a clinician determine real-time risk stratification and monitoring of treatment in an objective way.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Attia et al . [ 16 ] reported a significant association between obesity and higher mean obstructive index in patients with acute PE. In our study, patients with right heart dilatation (RV/LV ratio >1.2) were more likely to have larger clot volume as compared to those without RV dilatation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations